Intensitas Bermain Game Online, Minat, dan Prestasi Belajar Pendidikan Agama Islam di Sekolah Menengah Kejuruan - Khoiruddin, M Arif; Khoiruddin, M. Arif; Mudawwamah, Alfi Rohmatu (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2025)
This study aims to determine the relationship between the intensity of online game playing, learning interest, and Islamic Religious Education (PAI) learning achievement in Vocational High School (SMK) students. This study is based on increasing online game use among adolescents and the lack of empirical studies specifically highlighting its influence on interest and learning achievement in religious subjects. This study uses a quantitative approach with a correlational design. A sample of 82 grade X students of SMK PGRI 2 Kediri was randomly selected. The research instruments consisted of a questionnaire on the intensity of online game playing, a questionnaire on PAI learning interest, and documentation of Islamic Religious Education (PAI) report card grades. Data were analyzed using multiple linear regression. The results showed that learning interest had a significant positive effect on Islamic Religious Education (PAI) learning achievement (p < 0.05). In contrast, the intensity of online game playing did not show a significant effect. However, high intensity of online game playing has the potential to take up students' study time and does not provide tangible benefits to improving their learning achievement. The coefficient of determination (R²) of 0.248 indicates that the two variables explain 24.8% of the variation in Islamic Religious Education (PAI) learning achievement. These findings emphasize the importance of strengthening learning interest as a primary strategy in improving learning outcomes and the need for wise time management in digital activities such as online games.